2015
DOI: 10.1111/bcp.12632
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic interactions of a solid formulation of sodium oxybate and ethanol in healthy volunteers

Abstract: AIMThe pharmacologic effects of sodium oxybate (SO) have a number of similarities with those of alcohol. This study evaluated the pharmacodynamic interaction of SMO.IR (a solid immediate release formulation of SO) and alcohol (0.7 (males) or 0.57 (females) g kg -1 alcohol using 40% vodka). METHODSIn a randomized, double-blind, double-dummy, crossover trial, 24 healthy volunteers received randomly a) 2.25 g SMO.IR and placebo alcohol preparation, b) 2.25 g f SMO.IR and alcohol, c) 2.25 g SMO.IR matching placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Alcohol is a more common example in this field. This substance has a number of pharmacologic similarities with GHB at high doses but also differently marked effects, especially in human . In spontaneous human genetic disease affecting SSADH activity or in a similar model of SSADH −/− transgenic mice, an accumulation of GABA and GHB is observed in the cerebrospinal fluid (CSF).…”
Section: The Endogenous Ghb System In Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol is a more common example in this field. This substance has a number of pharmacologic similarities with GHB at high doses but also differently marked effects, especially in human . In spontaneous human genetic disease affecting SSADH activity or in a similar model of SSADH −/− transgenic mice, an accumulation of GABA and GHB is observed in the cerebrospinal fluid (CSF).…”
Section: The Endogenous Ghb System In Brainmentioning
confidence: 99%
“…This substance has a number of pharmacologic similarities with GHB at high doses but also differently marked effects, especially in human. [41][42][43] In spontaneous human genetic disease affecting SSADH activity 44 or in a similar model of SSADH −/− transgenic mice, 45,46 an accumulation of GABA and GHB is observed in the cerebrospinal fluid (CSF). This seems to indicate that when the access to the Krebs cycle is blocked, the synthesis of GABA and GHB is increased and the other routes for GHB degradation 47 are not active enough to maintain normal GHB concentrations.…”
Section: The Endogenous Ghb System In Brainmentioning
confidence: 99%
“…In addition, no side effects due to the combination of SMO 50 mg/kg and alcohol were observed in those SMO-treated alcoholics who were still drinking during the treatment [ 11 , 12 , 15 ]. This was also confirmed by a recent randomized, double-blind, double-dummy, cross-over trial in healthy volunteers aimed at exploring the pharmaco-dynamic interaction of the solid immediate release formulation of SMO and alcohol, which clearly showed that SMO and alcohol have separate adverse effect profiles, and that the objective effects of SMO are much less marked than those of alcohol, without any deleterious interaction [ 17 ]. However, larger clinical trials with alcohol dependent patients aimed at investigating a possible negative interaction during the concurrent intake of alcohol and SMO have not been performed, so that the suggestion not to drink during SMO administration represents a crucial message for physicians before prescribing this medication for AUD.…”
Section: Smo As An Anti-craving Drug To Treat Alcohol Use Disordermentioning
confidence: 64%
“…This study demonstrated a borderline significance in favor of SMO in reducing CAD [ 11 ]. Considering SMO as a possible treatment option for reducing alcohol consumption, concerns remain about the side effects of the combination with alcohol.No additional sedative effects induced by drinking during SMO treatment were found in healthy subjects [ 17 ]. Moreover, considering that SMO is utilized both for treating AWS and to maintain abstinence, according to clinical practice, then complete abstinence from alcohol should not be considered an exclusion criterion for treatment with SMO [ 14 ].…”
Section: Possible Role Of Smo In Reducing Alcohol Consumptionmentioning
confidence: 99%
“…Indeed, with respect to the single high dose of SMO used to induce sleep in narcoleptic patients (Alshaikh et al, 2012; Pardi and Black, 2006), or the intravenous administration for anaesthetic procedures, SMO doses employed to treat alcohol dependent patients are very low and fractioned up to six daily administrations, so that a sedation effect is never achieved (Cruz et al, 2004). Moreover, a recent randomized, double-blind, double-dummy, cross-over trial in healthy volunteers aimed at exploring the pharmacodynamic interaction of the solid immediate release formulation of SMO and alcohol has clearly shown that SMO and alcohol have separate adverse effect profiles, and that the objective effects of SMO are much less marked than those of alcohol, without any deleterious interaction (Pross et al, 2015). Consistently, we did not observe any additional sedative effect in our patients while drinking during the treatment with SMO.…”
Section: Discussionmentioning
confidence: 99%